Spectral and Electrochemical Sensing Studies of Unsymmetrical Schiff Bases having Enhanced Antifungal Activity - Shunmugaperumal, Selvaraj; Dhasarathan, Saranya; Selvaraj P, Kamatchi; Kaliappan, Ilango; Siva Kumar, Bathula (Asian Journal of Chemistry, 2021)
Novel unsymmetrical Schiff bases comprising azomethine spin-off having ferrocene moiety at one end and simple aromatic component attached imine at other end, capable of sensing multiple metal ions have been synthesized. The MLCT charge transfer band in UV-Visible studies upon coordination with metal ions with receptors is recorded particularly for Cu2+ ions. The observed ΔEp values with change in scan rate for metal free and metal added receptor solution suggest quasi-reversible process. Agar well diffusion method and molecular docking studies reveals that the synthesized compounds inhibit more efficiently fungi rather than bacteria, which hampers the progress of microbial research, as the available antifungal agents are minimal compared to antibacterial counterpart.